2006
DOI: 10.1111/j.1349-7006.2006.00320.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the protein gene product 9.5 promoter region in gallbladder cancer and its relationship with clinicopathological features

Abstract: Protein gene product 9.5 (PGP9.5) is a neurospecific peptide that removes ubiquitin from ubiquitinated proteins and prevents them being targeted for degradation by proteosomes. Its expression is a potential marker of non-small lung cancer, invasive colorectal cancer and esophageal squamous cell carcinoma. Gallbladder (GB) cancer is the most common malignant tumor of the biliary tract and is usually associated with gallstone disease, a late diagnosis, unsatisfactory treatment and a poor prognosis. To understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
(67 reference statements)
1
28
0
Order By: Relevance
“…PGP9.5 hypomethylation was found to be inversely correlated with the presence of a gallstone (P=0.015). These results suggest that PGP9.5 promoter hypomethylation could be a reliable marker for GBC and that DNA hypomethylation might play an important role in re-expression of the PGP9.5 gene in GBC [67].…”
Section: Epigenetic Changes In Gbcmentioning
confidence: 90%
See 1 more Smart Citation
“…PGP9.5 hypomethylation was found to be inversely correlated with the presence of a gallstone (P=0.015). These results suggest that PGP9.5 promoter hypomethylation could be a reliable marker for GBC and that DNA hypomethylation might play an important role in re-expression of the PGP9.5 gene in GBC [67].…”
Section: Epigenetic Changes In Gbcmentioning
confidence: 90%
“…A study from Korea [67], examined the methylation status of the promoter of PGP9.5 gene and its expression in surgical biopsy samples of 22 GBC, eight adenomas, 26 normal epithelia. Protein gene product 9.5 (PGP9.5) is a neurospecific peptide that removes ubiquitin from ubiquitinated proteins and prevents them being targeted for degradation by proteosomes.…”
Section: Epigenetic Changes In Gbcmentioning
confidence: 99%
“…This carcinoma is an aggressive tumor with a poor prognosis because of its inherent biology and often advanced stage at diagnosis [1,2], despite the recent advances in diagnostic modalities [3,4]. Curative surgical approaches remain the principal treatment associated with improvement in 5-year survival rates, but prognosis is closely correlated with the extent of tumor invasion and lymph node metastasis, suggesting survival is stage dependent (if carcinoma remains within the muscle layer and with no lymph node metastasis, the overall 5-year survival rate is about 90%) [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These 11 genes were selected because it has been reported that their promoters are methylated and their respective target mRNAs are silenced in gastric carcinoma (16)(17)(18)(19)(20)(21) and because some of them are known to be functionally related to metastasis, i.e., ADAM23, membrane adhesion and cell migration, CDH1, cell adhesion, FLNC, organization of actin polymerization and cell motility, ITGA4, cell-extracellular matrix, cell-cell interactions, THBS1, angiogenesis, and TIMP3, extracellular matrix degradation. Corresponding non-neoplastic mucosa and uninvolved lymph node tissues were included for control purposes, because some genes are frequently methylated in chronic gastritis and intestinal metaplasia, and because methylation has also been associated with aging (14).…”
Section: Introductionmentioning
confidence: 99%